The processes of strategy development - Bailey, Andy; Johnson, Gerry (Cranfield University, 1995)
This paper is concerned with the processes by which strategy is developed within organisations. It builds on research into the nature of strategy development being undertaken within the Centre for Strategic Management and Organisational Change at Cranfield School of Management. Initially the process of strategy development is discussed, a number of explanations of the process are presented and an integrated framework is developed. This framework is subsequently used to illustrate the strategy development process operating in a number of organisations. The implications for the strategic management process are discussed.